Enhanced Electron Transfer via the Interface Engineering of MoS2/MXene for Uranium Reduction and Organic Pollutants Degradation under Sunlight - Li, Shuyang (Langmuir : the ACS journal of surfaces and colloids, 2025)
Photocatalytic methods are extensively used in the treatment of uranium-containing wastewater. However, the reduction of uranium in natural sunlight remains a central challenge. This work proposed a MoS2 nanoflower-coupled Ti3C2 MXene reduction cocatalyst for bifunctional catalytic systems to remove U(VI) and degrade organic pollutants under natural sunlight. Advanced spectral characterization showed that MoS2/Ti3C2 had excellent photogenerated carrier transfer and light absorption capabilities. The experimental results show that when uranium and organic pollutants coexist, the removal rate of uranium is as high as 99%, and no sacrificial agents or inert gases are involved in this process. Further, theoretical calculations demonstrate that the bond behavior in the MoS2/Ti3C2 composites combines covalent bonds and ionic bonds, and about 0.497 electrons are transferred from Ti3C2 to the MoS2 monolayer. Two possible random adsorption interaction scenarios of [UO2·(H2O)5]2+ on MoS2/Ti3C2 composites are revealed meaningfully. The efficient removal of uranium and organic pollutants under real sunlight confirms the significant potential of the bifunctional photocatalyst for practical applications in radioactive wastewater